Death Rituals Among Tahtacıs of Adana Nergizlik Village (Journal of Alevism-Bektashism Studies, 2023)
In this study, the death-related rituals of the Tahtacis of the Hacı Emirli Ocağı living in the Nergizlik village of Adana’s Karaisalı district were evaluated in the context of transition periods of life. The subject of the study is the rituals that Tahtacıs create around death and how they give meaning to these rituals. In this sense, the symbolic, cultural and social meanings of the before, during and after death rituals of the Tahtacıs of Nergizlik village were evaluated and interpreted. The aim of the study is how Tahtacıs in Nergizlik village interpret the rituals related to death and how these meanings are formed. In addition, in the village of Nergizlik, the rituals of ikrar and musahiplik, which are the basic elements of Alevism in entering the path, are not practiced today. This is a factor in the Tahtacis in Nergizlik village giving meaning to their Alevi identity through death rituals. In addition to death being a transition period, the presence of many symbols in death-related rituals has been a factor in focusing on the meanings of these symbols in the research. Qualitative research method was used in the study. Purposive sampling technique was used to reach participants from whom rich data could be obtained about death-related rituals and the meanings of these rituals and to determine the sample. The sample of the research consists of 16 participants living in Nergizlik village and a total of 17 participants, including Dikme Dede, who takes part in the death-related rituals of Tahtacılar. All of the participants have been or are engaged in tree cutting, which is the traditional profession of Tahtacıs, at some point in their lives. Semi-participant observation and semi-structured in-depth interview techniques were used to collect data in the study. According to the data obtained from the participants, it was concluded that there are many rituals in the beliefs of the Tahtacıs of Nergizlik village regarding death and that the meanings related to these rituals are formed within social interaction in a certain process. It has been observed that Nergizlik Tahtacıs have preserved many traditions in their rituals related to death, but some rituals have changed from past to present. It has been concluded that some rituals, such as the sacrifice ceremony performed upon the death of the Musahip individual, have disappeared, and some rituals are in danger of extinction.